The Moderating Role of Environmental Factors In the Relationship between Dynamic Capabilities and Competitive Intelligence: A Field Study in Jordanian Pharmaceutical Firms Listed on the Amman Stock Exchange - Joma , Mahmoud (The Arab Journal of Administration, 2021)
This study aimed to investigate the Moderating Role of Environmental Factors in the Relationship between Dynamic Capabilities and Competitive Intelligence in Jordanian Pharmaceutical Firms listed on the Amman Stock Exchange. The study population consisted of all workers in Jordanian Pharmaceutical Firms listed on the Amman Stock Exchange from the three administrative levels (top management, middle management and lower management). The study sample included workers in the top and middle administrative levels (managers, deputies, assistants and heads of departments and supervisors) in Jordanian Pharmaceutical Firms listed on the Amman Stock Exchange at year 2018 totaling (193) individuals who were Purposive selected. To achieve the study objectives, the exploratory method was use to collect data from the sample, as well as using the descriptive method in presenting data and the analytical method in analyzing its results. The questionnaire was used to collect data, analyze it and test hypotheses using the SPSS. After conducting the necessary statistical analysis, the study reached a number of results, most notably that the Environmental Factors (Environmental Dynamism, Environmental Hostility and Environmental Complexity) play a moderating role in the effect of Dynamic Capabilities on Competitive Intelligence processes in Jordanian Pharmaceutical Firms listed on the Amman Stock Exchange. According to the results, the study recommended the Jordanian Pharmaceutical Firms need to benefit from the dynamic capabilities of their reflections on environmental factors in integration with competitive intelligence processes, by preparing an integrated study to clarify utilization levels of dynamic capabilities and competitive intelligence processes